A Theoretical Framework for Integrating BIM and Architectural Design to Advance Sustainable Infrastructure Development in Emerging Economies - Raed Farah,; Ahmad M. Abushab,; Ahmad M. Hamdan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This study develops a comprehensive theoretical framework that systematically integrates Building Information Modeling (BIM) into architectural design processes to enhance sustainable infrastructure development in emerging economies. Anchored in the context of Saudi Arabia’s Vision 2030, the framework is informed by sustainability theory, systems thinking, and established models of technology adoption and innovation diffusion. It conceptualizes BIM not merely as a digital tool but as a systemic enabler of environmentally responsible, socially inclusive, and economically viable design outcomes. The framework introduces a model that aligns regulatory inputs and sustainability goals with BIM-enabled processes and ESG-oriented outputs, reinforcing the triple bottom line. The paper contributes to the theoretical discourse by articulating the evolving roles of architects, engineers, and planners in digitally driven sustainability transitions, and by addressing institutional, organizational, and cultural barriers to BIM integration. It proposes strategic mitigation approaches including governance reform, capacity-building mechanisms, and interdisciplinary collaboration. The framework offers policymakers, academic institutions, and industry stakeholders a structured pathway to embed digital innovation into sustainable infrastructure agendas across the Global South.
Keywords: Building Information Modeling; Sustainable Infrastructure; Architectural Design Integration; Emerging Economies; ESG Transformation